2018
DOI: 10.3989/mc.2018.04717
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bagasse ash and recycled concrete aggregate on hardened properties of high-strength concrete

Abstract: ABSTRACT:This research aimed to use of bagasse ash as a cement replacement in high-strength recycled aggregate concrete (HS-RAC). Crushed limestone was replaced with 100% recycled concrete aggregate (RCA) and the ground bagasse ash (GBA) was used to partially replace ordinary Portland cement (OPC) at 20, 35 and 50%wt of binder to cast HS-RAC. The results indicated that the replacing of crushed limestone with RCA had a negative impact on the properties of the concrete. Increasing the amount of GBA in HS-RAC res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…• Durability of concrete containing RAs, including adopting RAs in HPC [86,87]: the durability properties of HPC that have been studied in literature included permeability, resistance to carbonation, and resistance to chloride penetration [88,89].…”
Section: 2keyword Analysismentioning
confidence: 99%
“…• Durability of concrete containing RAs, including adopting RAs in HPC [86,87]: the durability properties of HPC that have been studied in literature included permeability, resistance to carbonation, and resistance to chloride penetration [88,89].…”
Section: 2keyword Analysismentioning
confidence: 99%
“…In addition, Kapoor et al [ 125 ] demonstrated that the addition of MK was more effective in reducing chloride penetrability than equivalent SF addition. Emerging pozzolanic materials such as rice hull ash (RHA) [ 126 , 127 , 128 ], BA [ 129 , 130 ], palm oil fuel ash (POFA) [ 127 ], and palm oil clinker powder (POCP) [ 127 ] have also been proven to have superior effects in reducing RAC chloride ion permeability. In addition, Amiri et al [ 131 ] tried to use waste rubber powder as replacement for cement to improve the performance, but with little success (only 4–6%).…”
Section: Chloride Penetrationmentioning
confidence: 99%
“…The low specific gravity of BA and increasing BA content in the mix up to 10% results in the dust content in the mortar mix increasing, which results in a reduction in mortar density [43,45]. It was also stated that the higher quantity of the BA replacement of OPC by weight preceded an increase in paste volume, from which the density of BA was poorer than that of OPC, resulting in the lower density of the concrete [46].…”
Section: Densitymentioning
confidence: 99%